Teaching and Learning of Environmental Education - Geilson de Arruda Reis; Suzana Feldens Schwertner (Revista Diálogo Educacional, 2025)
Environmental Education (EE) has been recognized as a key component in building more sustainable societies. However, its inclusion in teacher education still faces challenges, often being limited to fragmented and sporadic approaches within the curriculum of Elementary and High school education. Addressing this gap, this article, resulting from a doctoral research in Teaching, proposed a study on EE with elementary school teachers, encouraging the creation and use of educational games. The objective was to analyze how participation in continuing education and the development of playful materials contributed to EE teaching practices. This qualitative study, with an action-research approach, was conducted in 2023 at a municipal school in Imperatriz, Maranhão, involving 17 volunteers. The research included a diagnostic questionnaire, five training sessions, and the creation of didactic games, which were later used by teachers to teach EE to students. Semi-structured interviews were conducted, and the data were analyzed using Discursive Textual Analysis. The teachers reported significant theoretical and practical learning from the training program, highlighting the importance of experiential approaches for the creation and application of educational games. The study underscores the fragility of EE in both initial and continuing teacher education and emphasizes the need for public policies that promote the systematic integration of EE into teacher training programs.